O germe da insurreição para além da metrópole: narrativas da participação e da luta popular em Antônio Pereira, Ouro Preto - MG - Polyana Pereira Coelho (2017)
The closing of the twentieth century in Brazil was accompanied by an intense expectation in the expansion of citizenship rights through the participation of social actors in the social transformation of the State. However, far from becoming a solution to the existing conflict of interests, when voicing collective demands in spaces before expressing the pressures of capital, representative democracy and the institutionalized model of participation have legitimated the modus operandi of the capitalist state, its instruments of domination and control. In relation to urban planning and city management, the various regulatory frameworks of urban policy and participatory instruments inaugurated with the "Citizen Constitution" (1988) and the City Statute (2001) did not serve to curb the process of peripheralization and to reduce socio-spatial segregation. Instead, in the 21st century, social tensions have increased considerably, sparking a global wave of popular demonstrations based on direct action and civil disobedience. In June of 2013, a cycle of demonstrations for social rights started in Brazil, and the mobilizations of vanguard social movements against the rise in transportation prices became countless. The occupation not only of streets, but also of institutional spaces became a constant. From these elements, we sought to analyze to what extent institutional shortcomings and contemporary experiences of collective action contribute to the emergence of counter-hegemonic projects and initiatives of community selforganization. In this context, we present the case of Antônio Pereira, district of Ouro Preto, MG. Located besides Bento Rodrigues, - sub-district of Mariana destroyed by the rupture of the dam of Fundão - the district is highly dependent on the mineral exploration and draws attention for the lack in infrastructure, urban equipment, and public services. However, following the national mobilization framework that opened in 2013, the district has been the stage of popular movements for better living conditions, demonstrating a rich awakening of subjectivities, capable of presenting important elements regarding the challenges of selforganization of popular movements. Using the method of collecting oral history, we narrate the scenarios of mobilizations, analyzing the motivations and the first unfolding events from the perspective of those who experience the local reality. The elaborations on direct action and institutional movements were guided by the necessary interconnection between these two spheres of both pressure and resistance, emphasizing the need for the self-organization of the working class to overcome the contemporary hegemonic order and for the construction of the right to the city in the Lefebvrian perspective of emancipation.